A acolhida na prática eclesial: reflexão a partir do encontro entre Jesus e Zaqueu - Lc 19,1-10 - Duarte, Laurinda Teresinha Moreira (2010)
The following research has as an objective thought about the importance of the Reception in the ecclesiastic s context, not simply by one strategy, but having as an paradigm the practice of Jesus Christ himself witch receive all. The reception that Jesus made with Zaqueu in the gospel of Lucas 19,1-10 is the subject of this paper. The subject is important, because in face of a globalized world, the encounter between the people, inclines to fragmentation, if reduces the new technologies language, like internet, minimize like this the personal encounter. The research reflects about the relation whit other people, the reception as one gesture that humanizes the relation between people. Jesus of Nazaré recover the sense of the integral reception of the human been, and from that, offers a possibility to live the fraternity between brothers. Jesus presents the humanity of the God (Father), with receive to all, with eyes of mercy and love. In the contemporary society, specify in the catholic s community, we look the necessity of humanize the relations between people. To Receive whit love and compaction, so the church became the receptions house, were yours members unite with Christ by the sacrament transmit by they on testimony and attitudes the practice of Jesus Christ affording by middle of the fraternal reception, the availability of the evangelization